Magnetic-size effects in ultrathin layers - Gummich, Ute; Cabrera, G. G.; Gonçalves da Silva, C. E. T.; Stein-Barana, Alzira C.M. [UNESP] (Elsevier B.V., 1993)
We study N-layer samples (N ≤ 10) for the Heisenberg model, with ferro- and antiferromagnetic exchange couplings, using a modified version of the Onsager reaction field approximation. The present scheme includes short-range spin-spin correlations, and allows for layer-dependent order parameters when free surface boundary conditions are imposed. The limits N = 1 (two dimensions) and N → ∞ (three dimensions) can be solved analytically, while systems with several layers have to be numerically calculated. We found no indication of a phase transition at finite temperature up to the sizes investigated (N = 10), the layered systems behaving essentially as two-dimensional. A phase transition is only obtained for the three-dimensional limit. © 1993.
Keywords: Antiferromagnetism; Correlation methods; Ferromagnetism; Magnetic couplings; Phase transitions; Temperature; Three dimensional; Heisenberg model; Layer dependent order parameters; Magnetic size effects; Onsager reaction field approximation; Spin-spin correlation; Ultrathin layer; Magnetic thin films